Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Quantifying nitrate dynamics in deep vadose zone under irrigated farmland in the North China Plain: Insights from continuous in-situ monitoring - Hanbing Jiang; Di Geng; Jiawei Fu; Meiying Liu; Yongqing Qi; Leilei Min; Shiqin Wang; Yanjun Shen (Agriculture, Ecosystems & Environment, 2026)

Characterization of Limosilactobacillus fermentum with the efficient conversion of fructose to mannitol and preparation of low-sugar juice - Yanjun Tong; Di Wang; Fang Sun; Rujie Liu; Ruijin Yang (Food Chemistry, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Preparation of macroporous Cu-SSZ-13-supported MOx catalysts and their catalytic performance for the simultaneous removal of soot and NOx - Lanyi Wang; Yanjun Chen; Shiwei Wang; Xinyu Chen; Shengran Zhou; Jiahong Li; Di Yu; Chunlei Zhang; Siyu Gao; Xuehua Yu; Chengyang Yin; Xiaoqiang Fan; et al. (Chemical Engineering Journal, 2025)

Chronic high temperature exposure, brain structure, and mental health: Cross-sectional and prospective studies - Wenxin Xiang; Keyi Lyu; Yanjun Li; Bo Yin; Limei Ke; Qian Di (Environmental Research, 2025)

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Estimation of Young’s modulus for rocks using a non-invasive CSAMT method - Muhammad Hasan; Yanjun Shang; Qingyun Di; Qingsen Meng (Bulletin of Engineering Geology and the Environment, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Release behavior of soluble salts in MSWI bottom ash used as road basement materials under continuous rainfall conditions - Lingqin Zhao; Dongming Zhang; Yanjun Hu; Qianqian Guo; Long Jiao; Nan Zhou; Francesco Di Maio (Waste Disposal & Sustainable Energy, 2023)

Key metabolites and mechanistic insights in forchlorfenuron controlling kiwifruit development - Yingying Bi; Chengkui Qiao; Lijun Han; Hanzhong Xie; Yanjun Xu; Di Wu; Ming Zhuang; Xinru Lv; Mengyuan Cao (Food Research International, 2023)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

An Objective Approach to Generating Multi-Physics Ensemble Precipitation Forecasts Based on the WRF Model - Chenwei Shen; Qingyun Duan; Wei Gong; Yanjun Gan; Zhenhua Di; Chen Wang; Shiguang Miao (Journal of Meteorological Research, 2020)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)

Statistical analysis of the relationship between spring soil moisture and summer precipitation in East China - Lei Meng; Di Long; Steven M. Quiring; Yanjun Shen (International Journal of Climatology, 2014)
The relationship between spring soil moisture ( SM ) and summer precipitation in East China (EC) was examined using monthly temperature and precipitation data and ERA ‐40 SM data. EC was divided into five different climate regions to investigate how SM ‐precipitation correlations vary under different climatic conditions. Both local and remote impacts of spring SM in EC were assessed. It was found that spring SM had significant correlations with summer precipitation in the East, Southeast, and Southwest regions, but not in the Northwest and Northeast region. This is possibly because correlations between summer precipitation and temperature (as a surrogate to SM –evaporation relationship) were statistically significant in the first three regions, but not in the Northwest and Northeast regions. Statistically significant positive correlations between SM and summer precipitation were found in the East and Southeast regions and statistically significant negative correlations were in the Southwest region. The negative SM ‐precipitation relationship is possibly because the Southwest region is primarily an energy‐controlled regime. Significant SM ‐precipitation correlations were usually associated with strong SM persistence and precipitation autocorrelation. Our results suggest that strong correlation between spring SM and summer precipitation might be due to the combination of SM –precipitation interactions and precipitation autocorrelation. Our study also demonstrated that there are strong temporal variations in SM –precipitation relationships in the regions where significant correlations occurred. May SM had significant positive correlations (approximately 0.6) with summer precipitation over most of the study period in East region. Strong negative correlation (approximately −0.6) was found in Southwest during 1980s‐1990s due to strong SM persistence and strong precipitation autocorrelation in the same period. This suggested that SM –precipitation relationships vary over time even in regions with strong coupling. Multivariate regression analysis demonstrated that SM persistence had the largest contribution to summer precipitation variation in East region and April precipitation was the dominant predictor of summer precipitation variations in Southeast and Southwest regions. Statistical analysis of SM and precipitation relationships should consider both SM persistence and precipitation autocorrelation. Results from this study can be used to improve the predictability of droughts.